2003
DOI: 10.3122/jabfm.16.4.318
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medical Practices: Training, Experience, and Attitudes of a Primary Care Medical School Faculty

Abstract: Background: Interest in alternative and complementary medical practices has grown considerably in recent years. Previous surveys have examined attitudes of the general public and practicing physicians. This study examined the training, experience, and attitudes of medical school faculty, who have the primary responsibility for the education of future family physicians.Methods: A 24-item, self-administered questionnaire was distributed to all 200 faculty at a medical school with a mission of training primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 11 publications
4
36
2
1
Order By: Relevance
“…Our physicians with <5 years' experience were more willing to refer patients, agreeing with a recent review by Kurtz et al [22] However, a review study with 19 surveys conducted between 1982 and 1995 found no differences in referral rates for CAM by age [20][21][22][23][24][25][26][27][28]. Two surveys [ 22,23] found referral rates for CAM were higher among female physicians and three found no difference in referral rates according to physician's gender [22][23][24].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our physicians with <5 years' experience were more willing to refer patients, agreeing with a recent review by Kurtz et al [22] However, a review study with 19 surveys conducted between 1982 and 1995 found no differences in referral rates for CAM by age [20][21][22][23][24][25][26][27][28]. Two surveys [ 22,23] found referral rates for CAM were higher among female physicians and three found no difference in referral rates according to physician's gender [22][23][24].…”
Section: Discussionsupporting
confidence: 81%
“…We found most physicians (58%) disapprove including CAM education in medical curricula, whereas most published surveys indicate physicians wish to learn about most common CAM therapies, a high proportion (62-81%) agreeing to receive more education on them [25][26][27] We report 60% oppose training allopathy physicians about CAM, unsurprising, since many of them respondents were at medical school and residency during which CAM wasn't widely discussed and rarely included in medical school curricula [28]. Most physicians disapprove CAM for patients refractory to allopathic treatment.…”
Section: Discussionmentioning
confidence: 81%
“…8 Studies have been undertaken in several countries to determine the knowledge and attitudes of medical, pharmacy, and nursing school students, staff members, and faculty members concerning CAM. [9][10][11][12][13] The majority of medical and pharmacy students surveyed welcomed the inclusion of CAM education in the curricula; nursing students were less enthusiastic. 6,[14][15][16][17] The increased use of CAM worldwide requires that consideration be given to the integration of CAM into health professions education.…”
Section: Introductionmentioning
confidence: 99%
“…Between 60-80% of surveyed physicians express interest in CAM therapy (Corbin Winslow & Shapiro, 2002;Milden & Stokols, 2004) but few as 14% have recommended it their patients. Among physicians there is prejudice about the different types if CAMs, established practices such as acupuncture, chiropractor tend to be surveyed as the most likely to be beneficial to the patient; While reiki, bioelectromagnetics, aromatherapy have been ranked by doctors as having the least potential to be beneficial or event harmful to the patient (Levine et al, 2003).…”
Section: Health Care Practitioners Attitude Towards Cammentioning
confidence: 99%